Searching Algorithm of Dormant Node in Wireless Sensor Networks - Feng, Bo; Tang, Wei; Guo, Guofa (International Journal of Online and Biomedical Engineering (iJOE), 2017)
In wireless sensor networks, the nodes around the base station have higher energy consumption due to the forwarding task of all the detected data. In order to balance the energy consumption of the nodes around the base station, a reasonable and effective mechanism of node rotation dormancy is put forward. In this way, a large number of redundant nodes in the network are in a dormant state, so as to reduce the load of important nodes around the base station. The problems of the redundant nodes in the sensor network are analyzed, and a new method is proposed to distinguish the redundant nodes based on local Delaunay triangulation and multi node election dormancy mechanism. The experimental results showed that this method could effectively distinguish the redundant nodes in the network; at the same time, through the multi round election mechanism, parts of redundant nodes are made dormant. In summary, they can reduce the network energy consumption on the condition of guaranteeing the original coverage.